Particulate matter measurements in Macedonia for health impact assessment - Rumrich, Isabell Katharina; M. Dimovska; D. GJorgjev; Lappi, Sari; Stefanovska, Aneta; Golubov, Nikola; Salonen, Raimo; Hanninen, Otto (Book of abstracts of the 22nd European Aerosol Conference, France Tours 2016, 2016)
Solid fuel combustion is a common heating source in Macedonia. Small scale combustion in combination with lacking legislation for other emissions lead to high air pollution levels in the Skopje valley. It is suspected that current air quality has significant impact on the population health. To investigate this topic further, risk assessment investigations have been introduced within the EU-funded Twinning project “Further strengthening the capacities for effective implementation of the acquis in the field of air pollution” (MoE 2016). Measured monthly mean concentration of particulate matter (PM) will be used in a pilot study on health impact assessment. The aim of the present work was to assess the correlations between the measured monthly particulate matter mass concentrations (PM2.5 and PM10) from different air quality monitoring stations, in order to evaluate their usability in the health impact assessment study. Method Monthly PM data were available from the national air quality monitoring network for the period of January 2012 to February 2016. PM2.5 was measured at two stations only (both within the city of Skopje) and PM10 at nine stations (4 Skopje city, 1 Skopje region, 4 outside Skopje region). Missing monthly values were imputed using the average PM2.5 or PM10 concentration calculated from measurements in the corresponding month of the other years at the same monitoring station. In addition, the average monthly ratios PM2.5:PM10 were calculated for the two stations in Skopje having parallel measurements of these two PM parameters with continuously acting instruments. Results The PM2.5:PM10 ratios at the two stations within Skopje city ranged between 0,61 in spring and 0,67 in autumn. Overall, the correlations in PM data between the different monitoring stations were high. The correlation in PM2.5 between the two stations in Skopje was excellent (R2>90%): The same applied to the PM10 stations within the city of Skopje, where only one monitoring station showed correlation lower than 90% with the others (Gazi Baba; R2>80%). all the Skopje region monitoring stations as well as the monitoring stations outside Skopje region showed generally intercorrelations higher than 70%. Only PM10 data from the station of Kavadarci, correlated poorly with the other stations. The rural background station of Lazaropole, located on a mountain, showed an inverse correlation with all the other monitoring stations. Conclusions. The limited size of the newly started national air quality monitoring programme in Macedonia poses challenges for air pollution exposure assessment. High PM2.5 and PM10 intercorrelations, however, suggest that the PM10 data can be used to improve spatial coverage of PM exposures. Most likely due to same sources, PM pollution levels have similar monthly profiles to those in Skopje city also at the three urban monitoring sites outside Skopje.
Keywords: Particulate matter; Health Impact Assessment; Macedonia